(untitled) (Revista Internacional de Formação de Professores, 2020)
Assessment is a way to improve environmental education (EE) processes. But there are no frequent assessment systems with a theoretical environmental educational foundation, adaptable to the contexts and that assess other scenarios in addition to learning. We propose a system based on the Complex Environmental Formation Theory. The proposal describes six scenarios in which EE processes express their complexity. We qualitatively study a school orchard experience and assess three of the scenarios. The results show an intermediate level of complexity. The conclusions are that the system is adaptable, and the case provides transferable elements.